Extraradical hyphae alleviate nitrogen deposition-induced phosphorus deficiency in ectomycorrhiza-dominated forests - Zhang, Ziliang (The New phytologist, 2023)
© 2023 The Authors. New Phytologist © 2023 New Phytologist Foundation.